History education and nation building : factors that shaped history education from 1959 to the 1970s - Ong, Shi Kai (2017)
This essay focuses on Singapore’s history education for primary and secondary students from 1959 into the 1970s. It proposes that history education was shaped by three factors during this period, the shift in educational direction, formulation of Singapore’s national history as well as the repression of Communism. With educational policies focused on language and science and technology, history education had to adapt to education’s shifting priorities. These shifting priorities reflected Singapore’s own nation building efforts and an appropriate national history had to be formulated to reflect this. The repression of Communism also become an integral part of nation building, permeating into both Singapore’s educational and political landscape. These three factors would alter and subsequently cement power relations between the Singapore government and its people. A rapidly reforming Singapore led to increasing state control over education. In turn, greater legitimization of the state through education was pursued. Such a cycle made increasing state hegemony possible as well. This hegemony would also play a part in the formulation of the history syllabus and the national identity it would espouse. Thus, the history syllabus and its development represented increasing state hegemony as Singapore’s nation building efforts took hold not only in education but economically and politically as well.